Effectiveness of acupuncture combined with auricular acupressure in the treatment of postoperative ileus: a study protocol for a randomized controlled trial - Lyu, Ruoyun; Wen, Zonglin; Huang, Rong; Yang, Zhiling; Chen, Yingqun (Frontiers in Surgery, 2024)
Background：About one-third of patients will meet postoperative ileus after abdominal surgery, which may cause various complications and hasn't been treated well in clinical.The comprehensive treatment of traditional Chinese medicine may be a good choice in promoting intestinal mobility. Therefore, the aim of this study protocol is to observe the effectiveness of acupuncture combined with auricular acupressure in decreasing incidence and related symptoms of POI.Methods: This is a single-center, assessor-blinded, randomized controlled trial.160 participants will be recruited in Shanghai Tenth People's Hospital and randomly divided into two paralleled groups with a 1:1 ratio. Intervention group will receive manual acupuncture combined with auricular acupressure, while control group will receive regular ERAS treatment. The primary outcome is time to first defecation and first flatus after surgery. The secondary outcomes include length of postoperative hospital stay, intensity of postoperative abdominal pain and distension, severity of postoperative nausea and vomiting, time to tolerated diet, inflammatory index and incidence of prolonged postoperative ileus.The results of this research will provide substantial evidence regarding the efficacy of comprehensive traditional Chinese treatment auricular acupressure and manual acupuncture in treating and preventing POI.